Immediate Analgesic Effect of Acupuncture in Patients With Primary Dysmenorrhea: A fMRI Study - Wang, Yanan; Xu, Jing; Zhang, Qing; Zhang, Qi; Yang, Ya; Wei, Wei; Guo, Xiaoli; Liang, Fanrong; Yu, Siyi; Yang, Jie (Frontiers in Neuroscience, 2021)
Primary dysmenorrhea (PDM) is a common gynecological disease characterized by lower abdominal pain. Acupuncture is considered a good alternative therapy for PDM. However, the central mechanism of the analgesic effect of acupuncture is largely unknown. In this study, eligible patients were randomized into the real and sham acupuncture groups using a computer-generated, permuted block randomization method. The study cohort comprised 34 patients: 19 in the real acupuncture group and 15 in the sham acupuncture group. The clinical characteristics of the patients during their menstrual period were collected, and imaging scans were performed during the first 3 days of the patients’ menstrual period. We analyzed task and resting functional magnetic resonance imaging (fMRI) data to investigate the potential central mechanism of the immediate effect of acupuncture intervention on the intensity of PDM pain. The task fMRI study found that the rostral anterior cingulate cortex (rACC) and right supplemental motor area were activated during real acupuncture. Using the resting-state functional connectivity (FC) method, we found a post- versus pre-treatment change in the FC of the rACC and left precentral gyrus in the comparison of real acupuncture versus sham acupuncture. In addition, the FC of the rACC–left precentral gyrus at baseline was negatively correlated with short-term analgesia, while the change in the FC of the rACC–left precentral gyrus was positively correlated with short-term analgesia after acupuncture treatment. These findings support the importance of rACC–left precentral gyrus resting-state FC in the modulation of the intensity of PDM pain through acupuncture, which may shed light on the central mechanism of acupuncture in the treatment of PDM.